The Cajal School in the Peripheral Nervous System: The Transcendent Contributions of Fernando de Castro on the Microscopic Structure of Sensory and Autonomic Motor Ganglia - de Castro, Fernando (Frontiers in Neuroanatomy, 2016)
The fine structure of the autonomic nervous system was largely unknown at the beginning of the second decade of the 20th century. Although relatively anatomists and histologists had studied the subject, even the assays by the great Russian histologist Alexander Dogiel and the Spanish Nobel Prize laureate, Santiago Ramón y Cajal, were incomplete. In a time which witnessed fundamental discoveries by Langley, Loewi and Dale on the physiology of the autonomic nervous system, both reputed researchers entrusted one of their outstanding disciples to the challenge to further investigate autonomic structures: the Russian B.I. Lawrentjew and the Spanish Fernando de Castro developed new technical approaches with spectacular results. In the mid of the 1920´s, both young neuroscientists were worldwide recognized as the top experts in the field. In the present work we describe the main discoveries by Fernando de Castro in those years regarding the structure of sympathetic and sensory ganglia, the organization of the synaptic contacts in these ganglia, and the nature of their innervation, later materialized in their respective chapters, personally invited by the editor, in Wilder Penfield's famous textbook on Neurology and the Nervous System. Most of these discoveries remain fully alive today.